Wear-resistant and corrosion-resistant titanium alloy material and preparation method thereof

By using laser melting and deposition technology in titanium alloy materials to prepare functional coatings and heat treatment, the AlSi phase and TiSi phase are formed, which solves the problem of insufficient wear resistance and corrosion resistance of titanium alloy materials in high friction and extreme environments. The bonding strength and performance of the material are significantly improved.

CN119194445APending Publication Date: 2024-12-27宁波尚材三维科技有限公司
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411606502.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-12
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

Traditional titanium alloys have insufficient wear resistance and corrosion resistance in high friction and extreme environments, and the coating and matrix bond strength are low, which affects the long-term reliability of the material.

Method used

The functional coating was prepared by laser melting deposition technology using titanium alloy powder, ceramic particles and silicon powder, and heat treatment was carried out at 450°C-650°C to form the AlSi phase and the TiSi phase to enhance the binding strength.

Benefits of technology

It significantly improves the wear resistance and corrosion resistance of titanium alloy materials, enhances the bonding between the coating and the substrate, and is suitable for high-end manufacturing fields such as aerospace, aerospace and medical care.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005129729160000131
    Figure BDA0005129729160000131
Patent Text Reader

Abstract

The invention provides a preparation method of a wear-resistant and corrosion-resistant titanium alloy material, the titanium alloy material comprises a titanium alloy base material and a functional coating, the functional coating is prepared from titanium alloy powder, ceramic particles and silicon powder, and the preparation method comprises the following steps: S10, weighing and ball-milling the titanium alloy powder, the ceramic particles and the silicon powder in sequence, preparing to obtain functional powder; s20, the functional powder is stacked on the surface of the titanium alloy base material in a laser melting deposition mode, and a titanium alloy complex is obtained; and S30, the titanium alloy complex is subjected to heat treatment for 4 h to 24 h under the condition that the temperature ranges from 450 DEG C to 650 DEG C, and the titanium alloy material is obtained. Wherein the ceramic particles comprise Al2O3; and the functional coating comprises an AlSi phase and a TiSi phase. According to the titanium alloy material prepared through the method, it is guaranteed that the titanium alloy material has good abrasion resistance and corrosion resistance in the severe environment, meanwhile, the functional coating is prevented from being peeled off, and the service life of the titanium alloy material is prolonged.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of titanium alloys, and in particular to a wear-resistant and corrosion-resistant titanium alloy material and a preparation method thereof. Background Art

[0002] Titanium alloys are widely used in high-end fields such as aerospace and medical devices due to their excellent strength, light weight and corrosion resistance. However, traditional titanium alloys have significant deficiencies in wear resistance and corrosion resistance, and are prone to wear and corrosion in high friction and extreme environments, which limits their application in harsh conditions. Although these properties can be partially improved by methods such as nitriding, anodizing and spraying of wear-resistant materials, they still face the problems of insufficient wear resistance and limited corrosion resistance.

[0003] In the prior art, titanium-based composite materials are prepared by adding hard particles (such as carbides and ceramic particles) to improve the wear resistance and corrosion resistance of the material. These particles are dispersed in the matrix and can significantly improve the friction performance. However, there is still a possibility that the bonding strength between the coating and the matrix may be insufficient, which may easily lead to the coating peeling or falling off. This delamination phenomenon is more obvious under high stress or high temperature environment, affecting the long-term reliability of the material.

[0004] Therefore, innovative preparation methods and material designs are urgently needed to ensure that titanium alloys have good performance in harsh environments while improving the bonding strength between the coating and the substrate. Summary of the invention

[0005] The invention relates to a wear-resistant and corrosion-resistant titanium alloy material and a preparation method thereof, aiming to enhance the wear resistance and corrosion resistance of the titanium alloy in a harsh environment while ensuring good bonding strength between a coating and a substrate.

[0006] In order to solve at least one of the above problems, the present invention provides a method for preparing a wear-resistant and corrosion-resistant titanium alloy material, wherein the titanium alloy material comprises a titanium alloy substrate and a functional coating, wherein the functional coating is prepared from titanium alloy powder, ceramic particles and silicon powder, and the preparation method comprises the following steps: S10: weighing and ball-milling the titanium alloy powder, ceramic particles and silicon powder in sequence to obtain a functional powder; S20: coating the functional powder on the surface of the titanium alloy substrate by laser melting deposition to obtain a titanium alloy composite; S30: heat treating the titanium alloy composite at a temperature of 450°C-650°C for 4h-24h to obtain a titanium alloy material; wherein the ceramic particles comprise Al2O3; and the functional coating comprises AlSi phase and TiSi phase.

[0007] Furthermore, the mass ratio of titanium alloy powder, ceramic particles and silicon powder is 7:(1.75-3):(2-4); and / or the particle size range of the titanium alloy powder is 20μm-60μm; and / or the particle size range of the ceramic particles is 20μm-50μm; and / or the particle size range of the silicon powder is 10μm-30μm.

[0008] Furthermore, step S10 specifically includes: weighing and mixing titanium alloy powder, ceramic particles and silicon powder in proportion, and then mixing them by planetary ball milling; wherein the ball-to-material ratio is 5:1, the rotation speed is 220rpm-300rpm, and the mixing time is 3h-6h.

[0009] Further, in step S20, the process parameters of laser melting deposition include: laser power of 200W-500W; and / or scanning speed of 0.5m / min-1.2m / min; and / or deposition thickness of each layer of 0.1mm-0.3mm; and / or laser beam diameter of 0.5mm-1.5mm.

[0010] Furthermore, after each layer is deposited, the titanium alloy substrate coated with the functional coating is preheated, and the preheating temperature is controlled to 100° C.-300° C., and the preheating duration is controlled to 15s-30s.

[0011] Furthermore, in step S20, microwave heating treatment is simultaneously performed while laser melting deposition is performed.

[0012] Furthermore, the process parameters of the microwave heating treatment include: an inert gas flow rate of 5 L / min-10 L / min; and / or a microwave initial power of 200 W-400 W; and / or a microwave operating power of 300 W-1500 W.

[0013] Furthermore, the heat treatment includes a first heating stage, a second heating stage and a cooling stage. The heating rate of the first heating stage is 20℃ / min-30℃ / min, the heating rate of the second heating stage is 70℃ / min-90℃ / min, and the cooling rate of the cooling stage is 5℃ / min-10℃ / min.

[0014] Furthermore, the titanium alloy substrate is Ti-6Al-4V; and / or the titanium alloy powder is Ti-5Al-5V-5Mo-3Cr.

[0015] The present invention also provides a wear-resistant and corrosion-resistant titanium alloy material, which is prepared by the above-mentioned preparation method.

[0016] After adopting the technical solution of the present invention, the following technical effects can be achieved:

[0017] The present invention relates to a wear-resistant and corrosion-resistant titanium alloy material and a preparation method thereof, which is intended to enhance the wear resistance and corrosion resistance of the titanium alloy in a harsh environment, and is suitable for high-end manufacturing fields such as aviation, aerospace, medical treatment and automobiles. The method mainly includes the composite preparation of a titanium alloy substrate and a functional coating, and the functional coating is composed of titanium alloy powder, ceramic particles and silicon powder. During the deposition process, the molten titanium alloy powder and the ceramic particles jointly form a layer of composite structure, which is evenly distributed in the molten titanium alloy matrix to improve the overall wear resistance and corrosion resistance. Among them, the silicon element will react with the titanium element and the ceramic particle Al2O3 under a high temperature environment, and the obtained AlSi phase can provide a certain strength and toughness. The obtained TiSi phase improves the wear resistance and interface bonding strength of the functional coating, and enhances the bonding strength between the titanium alloy substrate and the functional coating. Some ceramic particles will react with the titanium element in the titanium alloy substrate to obtain the TiAl phase, thereby effectively enhancing the bonding strength between the titanium alloy substrate and the functional coating and avoiding the peeling of the functional coating. DETAILED DESCRIPTION

[0018] In order to make the above-mentioned purposes, features and advantages of the present invention more obvious and easy to understand, the technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0019] An embodiment of the present invention provides a method for preparing a wear-resistant and corrosion-resistant titanium alloy material, wherein the titanium alloy material comprises a titanium alloy substrate and a functional coating, wherein the functional coating is prepared from titanium alloy powder, ceramic particles and silicon powder, and the preparation method comprises the following steps: S10: weighing and ball-milling the titanium alloy powder, ceramic particles and silicon powder in sequence to obtain a functional powder; S20: depositing the functional powder on the surface of the titanium alloy substrate by laser melting deposition to obtain a titanium alloy composite; S30: heat-treating the titanium alloy composite at a temperature of 450°C-650°C for 4h-24h to obtain a titanium alloy material; wherein the ceramic particles comprise Al2O3; and the functional coating comprises an AlSi phase and a TiSi phase.

[0020] The present invention relates to a method for preparing a wear-resistant and corrosion-resistant titanium alloy material, which is intended to enhance the wear resistance and corrosion resistance of the titanium alloy in harsh environments, and is suitable for high-end manufacturing fields such as aviation, aerospace, medical treatment and automobiles. The method mainly includes the composite preparation of a titanium alloy substrate and a functional coating, and the functional coating is composed of titanium alloy powder, ceramic particles and silicon powder. During the deposition process, the molten titanium alloy powder and ceramic particles together form a composite structure, which is evenly distributed in the molten titanium alloy substrate to improve the overall wear resistance and corrosion resistance. The additionally added silicon powder can promote the melting of ceramic particles to form a liquid phase, and also improve the bonding strength of the interface. The presence of silicon powder can form a reaction layer between the titanium alloy powder and the ceramic particles, thereby enhancing the bonding force.

[0021] When laser melts titanium alloy powder and ceramic particles, the temperature rises rapidly, making the titanium alloy powder and ceramic particles in a molten state. At this time, silicon reacts with titanium and ceramic particles Al2O3 under high temperature. On the one hand, silicon powder reacts with ceramic particles to obtain AlSi phase, such as Al4Si3O 12 , which can provide certain strength and toughness. On the other hand, silicon powder reacts with titanium in titanium alloy powder to obtain TiSi phase, such as TiSi2 and TiSi, which improves the wear resistance and interface bonding strength of the functional coating and strengthens the bonding strength between the titanium alloy substrate and the functional coating.

[0022] Furthermore, the above reactions are relatively rapid at high temperatures and can form a reaction layer in an instant. The formation of the reaction layer forms a transition zone between the titanium alloy powder and the ceramic particles, which contains a composite phase of titanium, silicon and oxides. The microstructure of the reaction layer will be multiphase, and may present fine grains and interlaced morphology, which will help improve the mechanical properties.

[0023] Furthermore, under high temperature conditions, some ceramic particles will react with the titanium element in the titanium alloy substrate to obtain the TiAl phase, thereby effectively enhancing the bonding strength between the titanium alloy substrate and the functional coating and preventing the functional coating from peeling off.

[0024] By weighing and ball-milling titanium alloy powder, ceramic particles and silicon powder to obtain a uniform functional powder, this ensures that the different components are fully mixed, thereby improving the performance of the coating; specifically, the ceramic particles provide excellent wear resistance, while the silicon powder helps to improve the bonding strength and corrosion resistance of the coating. Using laser melting deposition technology, the functional powder is precisely coated on the surface of the titanium alloy substrate to form a wear-resistant and corrosion-resistant functional coating. This technology can achieve the preparation of high-quality coatings in a relatively short time while controlling the thickness and uniformity of the coating. In addition, laser melting deposition technology provides an advanced coating preparation method. Through the laser deposition process, a uniform bonding and dense coating structure can be obtained, improving the overall mechanical properties and safety. The composition of the functional coating effectively improves the material's resistance to oxidation and corrosion, and is particularly suitable for applications in humid and chemically corrosive environments.

[0025] Furthermore, a surfactant can be added to the functional powder to improve the fluidity and mixing of the titanium alloy powder and the ceramic particles, thereby improving the uniformity during deposition. Surfactants such as polyvinyl alcohol (PVA) and polyvinyl pyrrolidone (PVP) can effectively reduce the cohesiveness of the functional powder.

[0026] It should be noted that in the prior art, aluminum powder is added to the functional coating to form an aluminum oxide film, which plays a role in protecting the substrate. However, the aluminum powder releases gas during the oxidation process, resulting in bubbles and defects in the coating formation process. Compared with aluminum powder, the present invention selects aluminum oxide particles as a component of the functional coating, wherein the aluminum oxide particles themselves have a higher hardness and can form a wear-resistant reinforcing phase in the coating, thereby improving the wear resistance of the material; in the case of damaged coating, the aluminum oxide particles can play a self-repairing role by generating an aluminum oxide film, and this protective film can prevent further corrosion and wear; under the preparation conditions of the present invention, the aluminum oxide particles have higher stability and are not prone to chemical reactions.

[0027] Heat treatment is carried out in the range of 450℃-650℃ to promote the phase transformation and organization optimization of the material. At this temperature, the precipitation of alloy elements such as Al and V can be promoted to enhance wear resistance, while avoiding phase transformation or phase decomposition caused by excessively high temperatures. The heat treatment time is set to 4h-24h, allowing the material to undergo sufficient phase transformation and organizational rearrangement at a suitable temperature, ensuring that the phases inside the alloy are fully precipitated and evenly distributed.

[0028] For example, at 550°C and 8h, the precipitation of TiAl phase can be promoted to enhance the bonding strength between the titanium alloy substrate and the functional coating, and the precipitation of TiSi phase can be promoted to improve wear resistance and strength, and the interface bonding strength is also improved. In addition, the size of the precipitated phase needs to be controlled between 200nm and 400nm to achieve the best strengthening effect.

[0029] By heat treating the titanium alloy composite at a specific temperature, the phase change and precipitate formation inside the material can be promoted, thereby improving the material's microstructure and mechanical properties. Reasonable heating and cooling rates help control the thermal stress of the material, avoid cracks or deformation caused by rapid changes, and ensure the performance stability of the material after heat treatment.

[0030] After the heat treatment, a chemical polishing treatment is also designed. The chemical polishing treatment uses chemical reactions to remove tiny bumps and uneven parts on the surface of the titanium alloy material, thereby obtaining a smooth and flat surface. The specific steps are: S41: Use a chemical polishing solution containing hydrofluoric acid and hexadecyltrimethylammonium chloride to thoroughly clean the titanium alloy surface to remove grease, dirt and other impurities. An ultrasonic cleaner can be used to ensure thorough cleaning; S42: Heat the chemical polishing solution to 50℃-80℃. If the temperature is too low, the reaction speed will be too slow. If the temperature is too high, it may cause excessive corrosion of the material. Controlling the temperature can increase the reaction rate and shorten the polishing time; S43: Immerse the titanium alloy material completely in the chemical polishing solution for 1min-10min; S44: Stir the solution to fully contact the titanium alloy surface. After polishing, rinse the workpiece with deionized water and then dry it.

[0031] Before the chemical polishing treatment, an activation treatment is also performed. The activation treatment uses a surfactant to activate the surface of the titanium alloy material, which plays a role of pre-polishing and can also promote the contact between the polishing solution and the material in the subsequent treatment. Among them, the surfactant is a composite surfactant composed of sodium dodecyl sulfate and polyvinyl alcohol, and the composite surfactant is an anionic and non-ionic composite surfactant. The composite surfactant cooperates with the hexadecyltrimethylammonium chloride used in the subsequent chemical polishing treatment, and can form a charged film layer through charge neutralization, which helps to improve the wettability of the surface, reduce the surface tension of the material, and avoid corrosion and oxidation of the material surface; in addition, the cationic surfactant can change the surface properties by adsorbing on the surface of the material, helping hydrofluoric acid to better react with the surface of the material.

[0032] Furthermore, after the heat treatment is completed, surface treatment can be performed, wherein the surface can be nitrided in a nitrogen environment to form a titanium nitride layer to further enhance wear resistance. In addition, the surface corrosion resistance can be enhanced and the surface finish can be improved by an electrochemical anodizing process.

[0033] In some embodiments of the present application, the mass ratio of titanium alloy powder, ceramic particles and silicon powder is 7: (1.75-3): (2-4); and / or the particle size range of the titanium alloy powder is 20μm-60μm; and / or the particle size range of the ceramic particles is 20μm-50μm; and / or the particle size range of the silicon powder is 10μm-30μm.

[0034] The mass ratio of titanium alloy powder, ceramic particles and silicon powder is 7: (1.75-3): (2-4). This ratio configuration is designed to balance the characteristics of the three materials so that the coating can maintain appropriate corrosion resistance and mechanical strength while enhancing wear resistance; a trace amount of silicon powder can promote good bonding between titanium alloy powder and ceramic particles. The particle size of titanium alloy powder is set at 20μm-60μm. Powders in this range can ensure good melting and bonding, and avoid poor fluidity caused by too small particle size. The particle size of ceramic particles is set at 20μm-50μm. Reasonable particle size helps to enhance the density and wear resistance of the coating. The particle size of silicon powder is set at 10μm-30μm. The smaller particle size of silicon powder can improve the wettability of the coating interface and enhance the bonding force.

[0035] In some embodiments of the present application, step S10 specifically includes: weighing and mixing titanium alloy powder, ceramic particles and silicon powder in proportion, and then mixing them by planetary ball milling; wherein the ball-to-material ratio is 5:1, the rotation speed is 220rpm-300rpm, and the mixing time is 3h-6h.

[0036] Titanium alloy powder, ceramic particles and silicon powder are mixed by planetary ball milling. Planetary ball milling helps to mix different materials efficiently and evenly, thereby ensuring their full combination. The ball-to-material ratio is set to 5:1, that is, the mass ratio of the ball milling medium to the powder mixture. The reasonable ratio effectively improves the mixing effect and grinding efficiency of the particles. The speed range during ball milling is set to 220rpm-300rpm. By controlling the speed, the mixing uniformity and particle refinement can be affected to ensure that the physical properties of the powder meet the expectations. The mixing time during ball milling is 3h-6h. This time range can ensure that all components can be fully mixed without causing excessive wear and affecting the material properties.

[0037] In some embodiments of the present application, in step S20, the process parameters of laser melting deposition include: laser power of 200W-500W; and / or scanning speed of 0.5m / min-1.2m / min; and / or deposition thickness of each layer of 0.1mm-0.3mm; and / or laser beam diameter of 0.5mm-1.5mm.

[0038] The laser power is set in the range of 200W-500W. The laser power in this range can effectively control the melting process and ensure that the material is fully melted without excessive heat input, thereby avoiding deformation and internal defects. The scanning speed is set in the range of 0.5m / min-1.2m / min. The appropriate scanning speed helps to control the heat input and cooling rate of the molten pool, ensuring good material bonding and uniformity of the microstructure. The deposition thickness of each layer is set to 0.1mm-0.3mm. This thickness range can achieve fine layered construction, ensure the strength and toughness of the material, and optimize production efficiency. The laser beam diameter is set in the range of 0.5mm-1.5mm. The choice of laser beam diameter affects the size of the melting area and the heat input, which helps to form a uniform molten pool and a fine coating structure.

[0039] By precisely controlling the laser power and scanning speed, the volatility of the molten pool can be reduced, the bonding of the molten material can be improved, and the overall quality of the coating can be enhanced. Reasonable deposition thickness and laser beam diameter can improve the microstructure of the coating and enhance its wear and corrosion resistance. Appropriate process parameter settings reduce the formation of defects such as cracks and pores caused by excessive heat input or excessive cooling speed, ensuring the reliability of the final product.

[0040] Furthermore, fiber lasers can be selected because of their high beam quality and high energy density. The laser melting deposition process can choose a cross-deposition path design to ensure that each layer of material can be fully melted and fused. In addition, after each layer is deposited, proper cooling and treatment can ensure good interlayer bonding and avoid cracks; the cooling process in the laser melting deposition process can adopt gas cooling, using nitrogen or helium as a protective gas to avoid oxidation.

[0041] It should be noted that the laser power of laser melting deposition is controlled within a relatively low range, which is more conducive to forming a dense, uniform, and high-strength deposition layer. More importantly, this condition can maximize the formation of the TiSi phase and help improve the interface bonding strength. Since the silicon powder selected in the present invention has a relatively small particle size and the scanning speed is not too fast, the laser power range selected in the present invention is sufficient to ensure that the functional powder is completely melted.

[0042] In some embodiments of the present application, after each layer is deposited, the titanium alloy substrate coated with the functional coating is preheated, and the preheating temperature is controlled to 100° C.-300° C., and the preheating duration is controlled to 15s-30s.

[0043] After each layer is deposited, the titanium alloy substrate coated with the functional coating is preheated. The preheating temperature is controlled in the range of 100℃-300℃, which helps to alleviate the temperature gradient and reduce the stress and deformation that may be caused during the cooling process. The duration of preheating is controlled in 15 seconds-30 seconds. The appropriate preheating time can ensure that the substrate fully reaches the set temperature, thereby improving the bonding strength of the coating.

[0044] During the laser melting deposition process, due to the repeated alternation of high-temperature melting and rapid cooling, a temperature difference will occur between the substrate and the coating, which will lead to the formation of stress and cracks. By preheating, the temperature gradient can be reduced, thereby reducing internal stress. Preheating helps to improve the contact state between the coating and the substrate, enhance the adhesion between the materials, reduce the risk of coating peeling, and thus improve the overall performance of the coating.

[0045] In some embodiments of the present application, in step S20, microwave heating treatment is simultaneously performed while laser melting deposition is performed.

[0046] By combining microwave heating with laser melting deposition, the deposition quality and performance of titanium alloy composites can be further improved, and more efficient material processing can be achieved. The powder material is melted by a high-energy laser and deposited layer by layer to form a structure. While laser melting deposition is taking place, microwave heating is used to heat the substrate. Microwave heating has the characteristics of high efficiency and rapid heating, and can achieve uniform heating during the deposition process.

[0047] Specifically, microwave heating uses electromagnetic waves to induce molecular motion in the material, rapidly raising the temperature. Compared with traditional heating methods, microwave heating has a faster heating rate and more uniform temperature distribution, which can effectively reduce the temperature gradient. Introducing microwave heating in the laser melting deposition process can perform additional heat treatment while the material is being deposited, helping to improve the performance of the material during the melting and cooling process.

[0048] In some embodiments of the present application, the process parameters of the microwave heating treatment include: an inert gas flow rate of 5L / min-10L / min; and / or a microwave initial power of 200W-400W; and / or a microwave operating power of 300W-1500W.

[0049] Microwave heating is used during the laser deposition process to increase the temperature of the ceramic particles and promote their bonding with the titanium alloy powder. The inert gas flow rate is set in the range of 5L / min-10L / min. The purpose of using inert gas is to avoid material oxidation during the heating process, while ensuring heat transfer and improving the degree of bonding. The initial microwave power is set in the range of 200W-400W. The adjustment of the initial power can achieve rapid initial thermal heating and improve the melting and bonding process of the material. The microwave operating power is set in the range of 300W-1500W. The adjustment of the operating power can accurately control the heating effect according to the actual deposition requirements to achieve the best deposition quality.

[0050] During microwave heating, the use of inert gas can effectively prevent the material from undergoing oxidation reaction in a high temperature environment, thereby maintaining the purity and performance stability of the material. Inert gases such as argon or nitrogen. Reasonable settings of microwave initial power and operating power can maintain heat supply during the deposition process, help control the temperature of the molten pool, optimize the melting and cooling process, and avoid material defects caused by overheating or too fast cooling.

[0051] A spheroidization process is also included between step S10 and step S20: S11: A radio frequency plasma generator is used and excited into plasma, and the functional powder is sent into the plasma source area. The melted functional powder is solidified into a sphere, and then cooled and collected. Among them, the radio frequency power is controlled between 3kW-6kW. Too high power will cause excessive melting and affect the particle shape, while too low power may not be able to effectively spheroidize the powder. The commonly used plasma gas is argon, with a flow range of 5L / min-20L / min. Hydrogen is also added to avoid oxidation of the powder. During the spheroidization process, the surface temperature of the powder needs to reach the micro-melting temperature, and the spheroidization time is designed to be between 2min-10min. The setting of the particle size range of the above-mentioned titanium alloy powder, ceramic particles and silicon powder also helps the spheroidization process, thereby ensuring that the functional powder forms a stable sphere.

[0052] Through RF plasma spheroidization treatment, the surface of the powder particles will become smooth due to surface tension, forming relatively uniform spherical particles. Spherical powder can not only improve the uniformity and density of the coating, but also reduce coating defects such as pores. After spheroidization, the fluidity of the powder particles is significantly improved, so that during the laser melting deposition process, the powder can be deposited more evenly on the substrate surface, improving the quality of the coating.

[0053] Before the spheroidization treatment, the functional powder can also be blown into a high-voltage electrostatic field using an airflow, so that the powder surface is charged. Due to the repulsive force between the charges, the powder remains dispersed during the radio frequency treatment and does not aggregate, and the obtained powder particle size is more uniform. In some embodiments of the present application, the heat treatment includes a first heating stage, a second heating stage, and a cooling stage. The heating rate of the first heating stage is 20°C / min-30°C / min, the heating rate of the second heating stage is 70°C / min-90°C / min, and the cooling rate of the cooling stage is 5°C / min-10°C / min.

[0054] The design of the heating and cooling rates in each stage aims to improve the bonding between the coating and the substrate, enhance the wear resistance and corrosion resistance, and ensure the mechanical properties and durability of the final material. Among them, the heating rate of the first heating stage is 20℃ / / min to 30℃ / min. The lower heating rate helps to gradually heat the material, avoid the accumulation of thermal stress caused by the rapid temperature rise, and ensure the uniformity and stability of the material in the initial heating stage. The heating rate of the second heating stage is increased to 70℃ / min to 90℃ / min. The purpose is to quickly heat the material to the target temperature range in a short time, which is used to quickly complete the specific phase transformation of the titanium alloy composite and improve the adhesion strength of the coating; more importantly, the AlSi phase and TiSi phase in the coating material are basically formed at this stage. The cooling stage is set to 5℃ / min to 10℃ / min. The thermal stress caused by the excessive temperature gradient is avoided by slow cooling, ensuring the close bonding between the coating and the substrate and reducing the generation of cracks or other defects.

[0055] In some embodiments of the present application, the titanium alloy substrate is Ti-6Al-4V; and / or the titanium alloy powder is Ti-5Al-5V-5Mo-3Cr.

[0056] As an α-β type titanium alloy, Ti-6Al-4V titanium alloy is suitable for manufacturing structural parts due to its good specific strength and toughness. Its high strength-to-weight ratio and excellent corrosion resistance make it widely used in aerospace, medical equipment and other industries. The composition of Ti-5Al-5V-5Mo-3Cr alloy powder not only improves the tensile strength, but also improves the stability and corrosion resistance in high temperature environments, and is particularly suitable for manufacturing parts requiring high thermal strength and wear resistance. In the present invention, the use of Ti-5Al-5V-5Mo-3Cr alloy powder can improve the melting efficiency and deposition quality of the powder, and can effectively improve the microstructure and performance of the material after heat treatment.

[0057] An embodiment of the present invention further provides a wear-resistant and corrosion-resistant titanium alloy material, which is prepared by the above-mentioned preparation method.

[0058] During the preparation process of this titanium alloy material, heat treatment and special alloy composition design are performed to significantly enhance the hardness and wear resistance of its surface. The chemical composition of the material and its heat treatment process are optimized, so that the titanium alloy has excellent corrosion resistance in various corrosive environments and can extend its service life. Specifically, by using Ti-6Al-4V as the substrate and Ti-5Al-5V-5Mo-3Cr as the powder, combined with a specific heat treatment process, the microstructure of the material is optimized, and the strength and toughness of the material under dynamic load are enhanced. By controlling the temperature, time and heating and cooling rates of the heat treatment, the performance of the titanium alloy material can be precisely controlled, so that it can achieve the best balance in wear resistance and corrosion resistance.

[0059] Example 1

[0060] An embodiment of the present invention provides a method for preparing a wear-resistant and corrosion-resistant titanium alloy material, comprising the following steps:

[0061] S10: Titanium alloy powder, ceramic particles and silicon powder are weighed and ball-milled in turn to prepare functional powder. The mass ratio of titanium alloy powder, ceramic particles and silicon powder is 7:2:3. The particle size range of titanium alloy powder is 30μm, the particle size range of ceramic particles is 30μm, and the particle size range of silicon powder is 15μm. Planetary ball milling is used for mixing, with a ball-to-material ratio of 5:1, a rotation speed of 220rpm, and a mixing time of 3h. The titanium alloy substrate is Ti-6Al-4V, and the titanium alloy powder is Ti-5Al-5V-5Mo-3Cr.

[0062] S20: The functional powder is deposited on the surface of the titanium alloy substrate by laser melting deposition to obtain a titanium alloy composite. The laser power is 300W, the scanning speed is 1m / min, the deposition thickness of each layer is 0.1mm, and the laser beam diameter is 0.7mm. During the deposition, microwave heating treatment is also used, the inert gas flow rate is 5L / min, the microwave initial power is 200W, and the microwave operating power is 600W. After each layer of deposition, the titanium alloy substrate coated with the functional coating is preheated, and the preheating temperature is controlled to 150°C, and the preheating duration is controlled to 30s.

[0063] S30: heat treating the titanium alloy composite at 450°C for 4 hours to obtain a titanium alloy material, wherein the heating rate of the first heating stage is 20°C / min, the heating rate of the second heating stage is 75°C / min, and the cooling rate of the cooling stage is 10°C / min.

[0064] Example 2

[0065] The embodiment of the present invention provides a method for preparing a wear-resistant and corrosion-resistant titanium alloy material. The specific steps are as shown in Example 1, except that:

[0066] In S10, the mass ratio of titanium alloy powder, ceramic particles and silicon powder is 7:3:4.

[0067] Example 3

[0068] The embodiment of the present invention provides a method for preparing a wear-resistant and corrosion-resistant titanium alloy material. The specific steps are as shown in Example 1, except that:

[0069] In S10, the particle size range of the titanium alloy powder is 50 μm, the particle size range of the ceramic particles is 50 μm, and the particle size range of the silicon powder is 30 μm.

[0070] Example 4

[0071] The embodiment of the present invention provides a method for preparing a wear-resistant and corrosion-resistant titanium alloy material. The specific steps are as shown in Example 1, except that:

[0072] In S20, after each layer is deposited, the titanium alloy substrate coated with the functional coating is preheated, and the preheating temperature is controlled to 300°C, and the preheating duration is controlled to 15s.

[0073] Example 5

[0074] The embodiment of the present invention provides a method for preparing a wear-resistant and corrosion-resistant titanium alloy material. The specific steps are as shown in Example 1, except that:

[0075] S30: heat treating the titanium alloy composite at 650°C for 20 hours to obtain a titanium alloy material, wherein the heating rate of the first heating stage is 30°C / min, the heating rate of the second heating stage is 90°C / min, and the cooling rate of the cooling stage is 5°C / min.

[0076] Comparative Example 1

[0077] The comparative example of the present invention provides a method for preparing a wear-resistant and corrosion-resistant titanium alloy material. The specific steps are as shown in Example 1, except that: there is no silicon powder in S10.

[0078] Comparative Example 2

[0079] The comparative example of the present invention provides a method for preparing a wear-resistant and corrosion-resistant titanium alloy material. The specific steps are as shown in Example 1, except that: the treatment in S30 is not performed.

[0080] The titanium alloy materials provided in the examples and comparative examples were subjected to performance tests: (1) wear resistance, using friction and wear tests to test their wear rate under high load; (2) corrosion resistance, using salt spray tests to evaluate their corrosion resistance in corrosive environments; (3) bonding strength, using tensile tests and peeling tests to determine the bonding strength between the deposited layer and the substrate. The test results are shown in Table 1.

[0081] Table 1 Wear and corrosion resistance test results of implementation examples 1-5 and comparative examples 1-2

[0082]

[0083] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. A method for preparing a wear-resistant and corrosion-resistant titanium alloy material, characterized in that: The titanium alloy material comprises a titanium alloy substrate and a functional coating, wherein the functional coating is prepared from titanium alloy powder, ceramic particles and silicon powder, and the preparation method comprises the following steps: S10: weighing and ball-milling the titanium alloy powder, the ceramic particles and the silicon powder in sequence to prepare a functional powder; S20: depositing the functional powder on the surface of the titanium alloy substrate by laser melting deposition to obtain a titanium alloy composite; S30: heat treating the titanium alloy composite at a temperature of 450° C. to 650° C. for 4 h to 24 h to obtain the titanium alloy material; Wherein, the ceramic particles include Al2O3; and the functional coating includes AlSi phase and TiSi phase.

2. The preparation method according to claim 1, characterized in that: The mass ratio of the titanium alloy powder, the ceramic particles and the silicon powder is 7:(1.75-3):(2-4); and / or The particle size of the titanium alloy powder is in the range of 20 μm to 60 μm; and / or The particle size of the ceramic particles ranges from 20 μm to 50 μm; and / or The particle size of the silicon powder is in the range of 10 μm to 30 μm.

3. The preparation method according to claim 1, characterized in that: The step S10 specifically includes: The titanium alloy powder, the ceramic particles and the silicon powder are weighed and mixed according to a certain proportion, and then mixed by planetary ball milling; Among them, the ball-to-material ratio is 5:1, the rotation speed is 220rpm-300rpm, and the mixing time is 3h-6h.

4. The preparation method according to claim 1, characterized in that: In step S20, the process parameters of the laser melting deposition include: Laser power is 200W-500W; and / or Scanning speed is 0.5m / min-1.2m / min; and / or The deposition thickness of each layer is 0.1 mm to 0.3 mm; and / or The diameter of the laser beam is 0.5mm-1.5mm.

5. The preparation method according to claim 1, characterized in that: After each layer is deposited, the titanium alloy substrate coated with the functional coating is preheated, and the preheating temperature is controlled to 100° C.-300° C., and the preheating duration is controlled to 15s-30s.

6. The preparation method according to claim 1, characterized in that: In the step S20, microwave heating treatment is simultaneously performed while the laser melting deposition is being performed.

7. The preparation method according to claim 6, characterized in that: The process parameters of the microwave heating process include: The inert gas flow rate is 5L / min-10L / min; and / or The initial microwave power is 200W-400W; and / or The microwave operating power is 300W-1500W.

8. The preparation method according to claim 1, characterized in that: The heat treatment includes a first heating stage, a second heating stage and a cooling stage. The heating rate of the first heating stage is 20°C / min-30°C / min, the heating rate of the second heating stage is 70°C / min-90°C / min, and the cooling rate of the cooling stage is 5°C / min-10°C / min.

9. The preparation method according to claim 1, characterized in that: The titanium alloy substrate is Ti-6Al-4V; and / or The titanium alloy powder is Ti-5Al-5V-5Mo-3Cr.

10. A wear-resistant and corrosion-resistant titanium alloy material, characterized in that: The titanium alloy material is prepared by the preparation method described in any one of claims 1 to 9.

Citation Information

Cited By

  • Heterogeneous phase titanium-based composite coating as well as preparation method and application thereof

    CN122610069A